ONLINE MARKETPLACE DAN TOURIST VIRTUAL COMMUNITIES DI INDUSTRI PARIWISATA (INOVASI DISRUPTIVE DALAM INDUSTRI PARIWISATA) - I Wayan Sukma Winarya Prabawa (Institut Pariwisata dan Bisnis Internasional, 2017)
The use of Technology, Information and Communication (ICT) with creative and innovative content has emerged various forms of product innovation with disruptive character. Millennial market share recently is regarded as a selective market and the actors who play a major role in the development and evolution of conventional products into new features products to respond the current needs of global society in which facilitating the ease of transactions between service providers and their consumers. This paper aims to describe the model and phenomenon of the emergence of ICT-based product innovation in the context of global tourism. Through literature review and qualitative research, it is concluded that the phenomenon is inevitable and has occurred earlier in developed countries. However the innovations have disrupted the dominating product for a long time yet this innovation have raised a new industry with benefits that cannot be underestimated to society.